Financial integration and total factor productivity: In consideration of different capital controls and foreign direct investment - Md Arif-Ur-Rahman; Kazuo Inaba (Journal of Economic Structures, 2020)
There is a long debate among policymakers and academicians regarding whether assessments of international financial integration have significant growth benefits and whether such benefits compensate for the accompanied risks. Recent financial crisis has revived this debate. The previous empirical studies have not been able to establish conclusive presumed benefits of financial integration for economic growth. This paper attempts to analyze the financial openness and total factor productivity (TFP) growth nexususing dynamic panel regression models for a substantial sample of countries ranging from year 1970 to 2014. Different measures of financial openness are incor-porated in the dataset. We find evidence that financial integration is associated with higher TFP growth. A range of integration measures (both de jure and de facto) shows robust association with financial integration and TFP growth. The result also suggests that financial development might reduce the marginal effects of financial integration on TFP growth. This finding, however, appears to be influenced by the recent global economic turmoil and excessive private finance, especially in recent years.
Keywords: F41; F36; F15; 330; International financial integration; Total factor productivity; Financial development; Economic turmoil